Cost-of-illness of patients with chronic hand eczema in routine care: results from a multicentre study in Germany - Augustin, Matthias; Kuessner, D.; Purwins, Sandra; Hieke, K.; Posthumus, J.; Diepgen, Thomas L. (British journal of dermatology, 2011)
Background It is broadly assumed that costs caused by chronic hand eczema (CHE) are significant. However, there is a lack of cost-of-illness studies on CHE. Objectives To determine the direct and indirect costs of CHE under routine conditions in Germany from the societal perspective. Methods A cross-sectional survey was conducted in 24 outpatient practices and clinics across Germany. Patients with CHE refractory to potent topical steroids and insured by statutory health insurance were eligible. Clinical and cost data were collected using standardized questionnaires. Severity classes were defined according to a photographic guide and physician global assessment (PGA). Four treatment stages were defined based on the German CHE guidelines: topical treatments only (stage I), additionally ultraviolet (UV) radiation therapy (II), systemic therapy (III) and inpatient treatment (IV). Bivariate associations between costs and severity as well as treatment stage were assessed. Results Two hundred and twenty-three patients with CHE (mean age 45·7 years, 56% women) enrolled in the study, of whom 63·2% were treated only with topical treatments, 15·7% additionally with UV radiation and 11·7% with systemic treatments. Of all patients, 9·4% had been admitted to hospital. Total costs per year and patient were € 2128, including € 1742 direct costs and € 386 indirect costs. The total costs increased with treatment stages I-IV (P < 0·001): € 1044, € 2307, € 2697 and € 8407, respectively. Accordingly, costs also correlated with clinical severity. Conclusions Patients with CHE refractory to topical steroids incur marked costs to society. The costs increase disproportionately with escalating treatment stages, especially in patients admitted to hospital. Hence, new treatments may help to reduce the societal costs of CHE.
Gesehen am 24.03.2022